Intention to get COVID-19 vaccines: Exploring the role of attitudes, subjective norms, perceived behavioral control, belief in COVID-19 misinformation, and vaccine confidence in Northern India - Fatema Husain; Md Ghazi Shahnawaz; Neda Haseeb Khan; Heena Parveen; Krishna Savani (Taylor & Francis Group, 2021)
This study examines people's intention to get COVID-19 vaccines and some of the psychological factors, that can facilitate the vaccination process. Using the theory of planned behavior (TPB) as a theoretical framework, we hypothesized that the key constructs of TPB (attitudes, subjective norms and perceived behavioral control) would explain people's intention to get COVID-19 vaccines. Belief in COVID-19-related misinformation and vaccine confidence were added to the TPB framework in order to comprehensively assess the predictors of COVID-19 vaccine intentions. Data was collected from 400 Indian respondents electronically during Feb-March, 2021. Hierarchical regression analysis was used to analyze the data. The Three components of TPB collectively explained 41% of the variance in the intention to get COVID-19 vaccines. Belief in COVID-19-related misinformation and vaccine confidence, on the other hand, had no significant impact on the intention to get COVID-19 vaccines. We discuss the theoretical and practical implications of these results.